Understanding microenvironments and the potential of traditional farming systems in a changing climate in Mexico and Belize - Hernandez Aguilar, Karla Gabriela (2025)
In Latin America and the Caribbean, climate change impacts have been particularly strongly felt by small-scale farmers who still practice farming that is highly dependent on rainfall and on traditional management. In the Yucatan Peninsula (Southern Mexico, Belize, and Northern Guatemala), these effects have particularly impacted Maya indigenous communities (Maya Yucatec) that practice traditional rain-fed agriculture. One of the traditional farming systems that continues to be practiced by the Maya people for millennia but has also been changing from its ancient origin is the Maya milpa or Kool (as referred to in Maya language). The Maya milpa is a polyculture system planted with a wide variety of plants (mainly maize, beans, and squash), managed in many ways under a biocultural approach, and characterized for supporting local food systems, social structures and the use of indigenous knowledge. Milpa has been of great scientific interest, not only because it has remained present in the livelihoods, culture, and local economy of Maya communities for centuries, providing income, food security, and cultural identity, but due to its vulnerability to extreme weather events such as droughts and hurricanes. Climatic variability, its impact on milpa, and how local societies adapt to climatic disturbances in this region has been explored by different authors. However, few studies have compared transnational adaptation responses within the same ethnic group practicing milpa and the role of indigenous knowledge in these adaptation strategies. This thesis investigates what aspects Maya Yucatec farmers prioritise when building resilience to climate change and how they use and adapt indigenous and other knowledge systems to develop this resilience. The research uses a convergent mixed methods approach to document, assess and compare similarities and differences in views, experiences and capacities within the Maya Yucatec people to explore the adaptation processes in traditional milpa and describes and analyses changes in local environmental conditions impacting milpa management. This study was conducted by drawing on data collected from eight case studies and 35 surveys with Maya Yucatec farmers in six communities in Mexico and Belize and empirical data on local weather and soil conditions. The results show that although sharing similar ethnicity, cultural background, environmental conditions, and livelihood patterns, Maya Yucatec farmers in the studied communities have remarkably different individual relationships with the milpa system. This farmer-milpa relationship has been shaped by historical processes and influenced by site-specific factors like social networks, interlinked with external factors. This has indirectly shaped milpa management and consequently their farming priorities, their adaptive capacity and their use of indigenous knowledge. Although climate stressors have influenced changes in milpa, there are other factors that have driven changes in milpa and vary across countries. In Mexico, changes have been shaped by social and cultural elements and networks, while in Belize key drivers were market demands and business trends. Within the past 30 years (1991-2021) different variable long-term monthly average precipitation and average temperature have been observed across three of the six communities studied. In terms of soil attributes, pH presented the lowest variability amongst the studied plots while phosphate, potassium, and particle size distribution showed the highest variability. Maya Yucatec farmers reported several, frequent, perceptible and situated changes in climate but variable precipitation and temperature appeared to be the most commonly perceived in both countries, which in most cases aligned with empirical data. When adapting and building resilience to climate change, Maya Yucatec farmers in Mexico and Belize use a combination of indigenous and modern knowledge. The use of indigenous knowledge remains active but can vary significantly depending on farmer’s individual priorities and thus its capacity to be regenerated, renewed, and adapted is different and autonomous. Similarly, this research found that Maya Yucatec farmers are using epistemological pluralistic approaches and reshaping indigenous and modern knowledges into an indigenous adaptive knowledge as a coping mechanism. The adaptation strategies implemented by Maya Yucatec farmers are heterogenous across both countries, but so is the knowledge embedded in these strategies. Changing or adjusting planting times, is perceived by farmers as the most reliable. Adaptation strategies are largely based on farmer’s individual knowledge and experiential learning in Mexico and on knowledge from external sources in Belize. Given that knowledge systems are a fundamental aspect of milpa management and of Maya Yucatec social identity, it can be inferred that climate change is also impacting social and cultural dynamics and driving cultural adaptation.